Nitrogen compounds balance and microbial protein synthesis in supplemented crossbred dairy cows in pasture (Acta Scientiarum. Animal Sciences, 2018)
The objective this work was to evaluate the supplementation of cows on Brachiaria decumbens pasture during the rainy-dry transition. Eight 1/2 Holstein/Zebu cows (497 ± 50 kg) were distributed in two 4 x 4 Latin squares, with 2 x 2 factorial treatments (100% mineral salt versus nitrogen salt containing 25:25:50% urea: corn: mineral salt, and 1.5 versus 3.0 kg d-1 concentrate per cow). The experiment lasted 56 days, divided into four periods of 14 days, the last seven days for data collection. No interaction effect (p > 0.05) was detected between the supplement and the different levels of concentrate for any of the evaluated variables. No effect (p > 0.05) of supplement or concentrate level was observed on urinary excretions of purine derivatives, microbial nitrogen compounds and microbial efficiency. Nitrogen salt increased (p < 0.05) nitrogen intake and increased urinary nitrogen excretion, leading to a reduced nitrogen balance, while the higher concentrate level increased (p < 0.05) nitrogen intake and the total amount of nitrogen excreted in milk. Therefore, it is recommended, for crossbred cows in the rainy-dry transition period, the supply of 1.5 kg d-1 concentrate during milking, using only mineral salt instead of nitrogen salt at will on pasture.